Self Managing Heart Failure in Remote Australia - Translating Concepts into Clinical Practice - Iyngkaran, Pupalan (Curr Cardiol Rev, 2016)
Congestive heart failure (CHF) is an ambulatory health care condition characterized by episodes of decompensation and is usually without cure. It is a leading cause for morbidity and mortality and the lead cause for hospital admissions in older patients in the developed world. The long-term requirement for medical care and pharmaceuticals contributes to significant health care costs. CHF management follows a hierarchy from physician prescription to allied health, predominately nurse-led, delivery of care. Health services are easier to access in urban compared to rural settings. The differentials for more specialized services could be even greater. Remote Australia is thus faced with unique challenges in delivering CHF best practice. Chronic disease self-management programs (CDSMP) were designed to increase patient participation in their health and alleviate stress on health systems. There have been CDSMP successes with some diseases, although challenges still exist for CHF. These challenges are amplified in remote Australia due to geographic and demographic factors, increased burden of disease, and higher incidence of comorbidities. In this review we explore CDSMP for CHF and the challenges for our region.